Ordo-Responsibility - Conceptual reflections towards a semantic innovation - Markus Beckmann; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2006)
Based on economic ethics, this paper reflects on and aims to improve the semantics of responsibility. The traditional concept of responsibility is threatened with erosion when responsibility is attributed to an actor who is unable to exercise individual control over the outcome of his actions. In the modern world-society this is increasingly the case. The concept of ordo-responsibility is helpful in identifying a suitable approach for the attribution and acceptance of responsibility. The perspective of economic ethics systematically differentiates between the initial basic game of business and the related meta-games of politics and public discourse. In this way, the focus shifts to the rule-setting processes and rule-finding discourses for which the actors can accept governance responsibility and discourse responsibility, respectively. These two forms of ordo-responsibility demonstrate a characteristic which is extremely important for processes of 'New Governance': they can be attributed to corporative actors, and they can be perceived by them in their own well-reflected interests.
urn:nbn:de:gbv:3:2-1349
Keywords: 330